Seeds of Extremism Amoung Student of Muhammadiyah School of Yogyakarta - Arif Budi Raharjo; Imam Mawardi; Dian Dwi Okaputra (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to answer the suspicion that there are seeds of extremism in the practice of Islamic education, especially in the formal education path at the primary and secondary education levels. To test the veracity of this allegation, this research was designed in the form of a survey conducted by measuring the level of moderation of students' religiosity in several Muhammadiyah schools of Yogyakarta. The research instrument was arranged using a Likert scale which measures on three dimensions of religious moderation: social action, conceptual chomprehention and belief (Faith). Descriptive quantitative analysis is used to describe the level of moderation of 372 respondents of this cross-sectional study. The results showed that 38% of students had religious moderation in the high category and the rest were medium (60%). It is known that the medium and high level of student religious moderation is more or less determined by the role of the teacher who is still used as the main source for students in obtaining Islamic religious knowledge (50%).